Sildenafil, pulmonary hypertension and bronchopulmonary dysplasia. (November 2016) - Herbert, S.; Tulloh, R.
Abstract: Pulmonary hypertension (PH) secondary to bronchopulmonary dysplasia (BPD) in infants remains a serious concern and continues to cause significant morbidity despite improvements in both quality of life and survival for patients. One of the potential agents that might help is sildenafil citrate, a phosphodiesterase-V inhibitor used a first line therapy for idiopathic PH. However, only limited evidence exists for its use as either monotherapy or part of a combination approach towards the management of PH in BPD. The evidence and current knowledge is presented for sildenafil alone and in combination with other disease modifying agents to treat PH in the presence of BPD. We have previously suggested that sildenafil appears to be safe and possibly effective in this condition. We present the evidence that if continued until PH resolution, there might be reduced mortality in this debilitating disease.